2022
DOI: 10.1155/2022/5009395
|View full text |Cite
|
Sign up to set email alerts
|

Sex Difference in the Association of Osteoporosis and Osteopenia Prevalence in Patients with Adrenal Adenoma and Different Degrees of Cortisol Excess

Abstract: Objective. Osteoporosis and osteopenia (OS/OP) are frequent in patients with adrenal adenomas associated with cortisol excess (CE). However, the relationship between OS/OP and CE severity considering sex differences is unknown. Design. A cross-sectional observational study from January 2006 to December 2015. Patients. 237 patients with adrenal adenoma associated with CE, including Cushing’s syndrome and mild autonomous cortisol secretion (MACS), diagnosed in 10 referral centers in Japan. MACS was defined by 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…Older studies [17][18][19][20][21][22][23][24][25][26][27][28][29] with a 1-mg DST cortisol cut-off > 3 mcg/dL showed a highly variable prevalence of vertebral fractures ranging from 43% to 100%. More recent studies performed with 1-mg DST cortisol cut-off >1.8 mcg/dL (50 nmol/L) [3,4,[30][31][32][33], demonstrated similar rates regardless of the size of the cohort, with fracture prevalence in larger cohorts ranging from 31.7% to 62.6% (Table 1).…”
Section: Fracture Prevalence In Patients With Macsmentioning
confidence: 84%
“…Older studies [17][18][19][20][21][22][23][24][25][26][27][28][29] with a 1-mg DST cortisol cut-off > 3 mcg/dL showed a highly variable prevalence of vertebral fractures ranging from 43% to 100%. More recent studies performed with 1-mg DST cortisol cut-off >1.8 mcg/dL (50 nmol/L) [3,4,[30][31][32][33], demonstrated similar rates regardless of the size of the cohort, with fracture prevalence in larger cohorts ranging from 31.7% to 62.6% (Table 1).…”
Section: Fracture Prevalence In Patients With Macsmentioning
confidence: 84%
“…The mentioned studies used various endocrine criteria in order to define the cortisol excess as seen in ACS (or equivalent) [ 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 ]. ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…As mentioned, ACS (or SCS or SH) involves a distinct type of tumour with positive (yet mild, not overt) cortisol (persistent) excess, and consecutive DXA-BMD evaluations depend on the criteria for defining this hormonal activity, on the age and sex of the studied population (including the menopausal status of women), and on the sample size of the cohort. Except for three, 37 cohorts provided data in terms of DXA and/or VFs [ 43 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 ], and a confirmation of a negative impact of bone status was generally confirmed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The previous studies showed that the female sex is a risk factor related to osteoporosis and is associated with a lower BMD. [21][22][23][24] Osteoporosis has a significant hormonal influence, particularly in postmenopausal women, where reduced estrogen levels have a negative effect on the formation of the bone by increasing the sensitivity to the bone resorption effect of parathyroid hormone. This can cause rapid bone loss as compared to bone formation leading to osteoporosis.…”
Section: Discussionmentioning
confidence: 99%